2006
DOI: 10.1111/j.1365-2109.2006.01569.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using different types of organic animal manure on plankton abundance, and on growth and survival of Tilapia rendalli (Boulenger) in ponds

Abstract: An experiment was conducted to evaluate the effect of using different types of organic manure on the plankton abundance, and growth and survival of Tilapia rendalli juveniles in ponds. Fish weighing 18.15±0.44 g were stocked into 12, 20 m2 ponds at 2 fish m−2 (40 fish pond−1). There were three replicate ponds per treatment (chicken manure, cattle manure, pig manure, and no‐manure as a control). After 84 days the T. rendalli in the chicken manure treatment were significantly larger and had higher net annual yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 24 publications
0
33
2
Order By: Relevance
“…The high nutritional value of phytoplankton in ponds generally account for a large share of total fish survival, condition factor and growth. Phytoplankton contain significant amount of protein ranging from 120 to 350 g kg −1 , lipids 72 to 230 g kg −1 and carbohydrates from 82 to 87 g kg −1 on a dry matter basis (Kang’ombe et al 2006). Likewise, Abou et al (2013) found the levels of protein, carbohydrate and lipid in natural food organisms to be as higher as 511, 273 and 77 g kg −1 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The high nutritional value of phytoplankton in ponds generally account for a large share of total fish survival, condition factor and growth. Phytoplankton contain significant amount of protein ranging from 120 to 350 g kg −1 , lipids 72 to 230 g kg −1 and carbohydrates from 82 to 87 g kg −1 on a dry matter basis (Kang’ombe et al 2006). Likewise, Abou et al (2013) found the levels of protein, carbohydrate and lipid in natural food organisms to be as higher as 511, 273 and 77 g kg −1 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A such of relation has been demonstrated and confirmed before through many studies by McQueen et al (1989), Vanni et al (1990), Lazzaro & Lacroix (1995) who have found a positive correlation between the enrichment in nutrients and the phytoplankton biomass and then between phytoplankton biomass and the one of zooplankton. The utilization of organic fertilizer has a positive effect on the phytoplankton and zooplankton abundance (Geiger, 1983;Kang'ombe et al, 2006). The zooplankton production in fertilized ponds with organic fertilizer shows that chlorophyll a and zooplankton rates are higher in these ponds than in the control (Geiger, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Milstein et al (1988) reported a minor influence of manure on fish yield compared to other management factors like stocking density and weight. Kang'ombe et al (2006) reported a high yield of fish due to application of different organic manure in earthen ponds. In this study although a high dose of green manure was applied it did not produce enough nutrients into the ponds to maintain the total fish biomass by increasing the natural pond production.…”
Section: Discussionmentioning
confidence: 99%